Pembuatan Automatic Sterilizer Chamber Sebagai Upaya Pencegahan Penyebaran Pandemi Covid-19 - Doni Abdul Fatah (Jurnal Ilmiah Pangabdhi, 2021)
The disease caused by the Corona Virus (Covid-19) is a disease that is transmitted through small droplets that are produced when an infected person coughs, sneezes, or exhales. This droplet cannot stay in the air for a long time, so it quickly falls and sticks to the surface of the floor, hands, or others. Besides, it can be transmitted when someone touches the surface of a contaminated object and then touches the eyes, nose, or mouth. A series of government efforts were taken to minimize the spread of this virus, starting with policies to limit activities outside the home, restricting schools, working, and implementing large-scale regional quarantines, all of which were carried out to reduce the spread of Covid-19. Through the community service program carried out by lecturers and students in contributing to solving problems in society by making Automatic Sterilizer Chambers, the existence of this tool is able to help the local community in dealing with its spread, which can be seen from the good response given by the community or local officials. This was evidenced by the enthusiasm of the participants who came to use the tool either at the village hall, school, or in other public places.